Systematic Literatur Review: Peran Kinerja Lingkungan pada Pengaruh Gender Diversity terhadap Kinerja Keuangan - Robby Sagara; Lola Cahaya Seri Rahayu; Pinia Tri Rahma (Journal of Creative Student Research, 2025)
This study aims to analyze the role of environmental performance in the relationship between gender diversity and corporate financial performance. The method used was a Systematic Literature Review (SLR) of reputable scientific articles and accredited national journals for the 2021–2025 period. The study results indicate that gender diversity has the potential to improve financial performance, but this effect depends on the company's environmental performance. Good environmental performance strengthens the contribution of gender diversity in sustainability-oriented strategic decision-making, thus positively impacting financial performance. Conversely, in companies with low environmental performance, the implementation of gender diversity tends to be symbolic and has not yet had a significant financial impact. These findings emphasize the importance of integrating inclusive governance and environmental management to create sustainable corporate value. This study provides insights for practitioners and policymakers regarding the importance of combining gender diversity with environmental initiatives to support sustainable corporate performance. These findings are important for business practitioners and policymakers in developing policies that support gender diversity and environmental sustainability to achieve better financial goals.